INTERNATIONALIZATION TOWARD INTERNATIONAL SUCCESS OF INDONESIAN SMALL AND MEDIUM ENTERPRISE: LESSONS FROM AUSTRALIAN PRACTICE - , Ida Bagus Putu Oka Suryawan, SE ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper planned to benchmark the level of internationalization of small and medium-sized enterprises in two different types of countries. Indonesia as one of developing countries will be contrast with Australia which represents the developed countries. The background of the study is based on the importance of small and mediumsized enterprise as the pillars in enhancing national economy. Therefore, understanding the development of SMEs by learning from Australian SMEs practice will be significant in answering globalization challenge in terms of internationalization. Moreover, the study aims to provide details in improving the industry as well as the entrepreneur and government bodies for better performance. Hence, the study found that Indonesian SMEs should improve significantly in its human resources in term of information and knowledge of the market as well as entrepreneurship characters.